Kualitas Angka Kuman Udara Pada Ruang Persalinan Praktik Bidan Swasta Di Kota Banjarbaru - Munawar Raharja (Poltekkes Kemenkes Banjarmasin Jurusan Kesehatan Lingkungan Banjarbaru, 2015)
Abstract : Microbial air count quality in the delivery room of midwife private practices in Banjarbaru City. The increasing role of private health care in the community, including midwife in private practice. The absence of rules on the environmental health of the midwife private practice led to a lack of sanitary supervision in the delivery room. A large number of microbial air in the delivery room can cause infection directly or indirectly through contaminated equipment used in the delivery process. To assess the microbial air count quality, state of health of the delivery room environment and determine the relationship between the quality of physical environment, physical building, and sanitation delivery room with microbial air count quality in the delivery room of midwife private practices in Banjarbaru City. This research used cross sectional survey design. The subject were all over the delivery rooms practices in Banjarbaru City midwife private with the inclusion criteria was still active, had a license, a separate private practice with a family room and were willing to participate in the study, namely 34 the delivery rooms. Data analysis was performed with the statistical analysis of univariate, bivariate with chi-square test and multivariate logistic regression analysis and descriptive data was analyzed by comparing the theoretical and applicable standards. A total of 29.4% the delivery rooms with the microbial air quality and 70.6% delivery rooms does not qualify. There were three variables associated with the study of microbial air quality, namely : the arrangement of the rooms, air circulation, and sanitary rooms. There is a significant relationship among the arrangement of the room, sanitary room, and air circulation to the microbial air quality in the delivery room, and the delivery room air circulation is a variable that contributes most greatly to the microbial air count quality in the delivery room midwife private practices in Banjarbaru City Key words : air microbial, environmental health, delivery room, midwife